Penerapan Strategi Pembelajaran Think Talk Write (TTW) Dalam Upaya Meningkatkan Hasil Belajar Muatan Pelajaran Matematika Siswa Kelas VI Sekolah Dasar Negeri 4 Seraya Barat - I Wayan Suada (Cetta: Jurnal Ilmu Pendidikan, 2021)
This research is motivated by the low learning of grade VI students of SDN 4 Seraya Barat in the content of mathematics lessons, this is thought to be caused by several factors, including: learning that is still theoretical so that students will easily feel bored and bored in receiving learning and in teacher learning more dominate the activity, so that it can eliminate students' enthusiasm for mathematics learning material. This classroom action research was carried out in two cycles with the aim of improving learning outcomes of mathematics lessons. The subjects of this study were 18th graders of SDN 4 Seraya Barat, consisting of 7 female students and 11 male students. Data were collected by learning outcomes tests. The collected data was then analyzed by qualitative descriptive statistics. The results showed that the application of the Think Talk Write (TTW) learning strategy in learning mathematics content could increase student learning outcomes, student learning outcomes in cycle I were 71.85 and student learning outcomes in cycle II were 84.07. Thus there was an increase of 12.22 from cycle I to cycle II.